REPRESENTASI KEKUASAAN DALAM TUTURAN ELIT POLITIK PASCAREFORMASI: Pilihan Kata dan Bentuk Gramatikal - Johar Amir (Masyarakat Linguistik Indonesia, 2013)
The qualitative research is aimed at describing the power representation of the political elite at the national level through: (1) word choices expressed by the political elite in representing their power, and (2) grammatical forms used by the political elite. The data of the research were the words of the political elite at the national level in Indonesia. The findings show that the word choice used by the political elite involved the use of foreign terms, word classification in the political field, and sentence structures containing sentence modes, metaphors, parables, climaxes, and repetitions.